Analisis Economic Value Added (Eva) dan Market Value Added (MVA) Sebagai Alat Ukur Kinerja Keuangan Bank Umum Swasta Nasional (BUSN) Devisa Go Public Tahun 2014 - 2018 - Susanti Ifa; M Dimyanti; N K Sari (Universitas Pendidikan Ganesha, 2020)
Investor invests in a company to make a profit in the future. Financial performance of a company can be evaluate and count from the annual financial statements of the company. There are several methods that can be used in measuring the financial performance of companies, one of which is to use a value based approach. The purpose of this research is to find out the differences in financial performance on the Foreign Exchange Banks. Value based approach used in this research is Economic Value Added (EVA) and Market Value Added (MVA). Based on the calculations and analysis that Economic Value Added (EVA) and Market Value Added (MVA) Bank Foreign Exchange Banks were not good enough. This was proved by several Banks that obtained a value of Economic Value Added (EVA) and Market Value added (MVA) have negative result. From the entire sample, Bank Central Asia, Tbk holds the highest EVA and MVA value. The differences in financial performance with ANOVA (One Way) are known to have a significant difference in Foreign Exchange Banks.